The influence of lighting on fingerlings counting - Garcia, Vanir; Sant’Ana, Diego André; Zanoni, Vanda Alice Garcia; Pache, Marcio Carneiro Brito; Naka, Marco Hiroshi; Albuquerque, Pedro Lucas França; Lewandowski, Tiago; Oliveira Junior, Adair da Silva; Rozales, João Victor Araújo; Ferreira, Milena Wolff; Queiroz, Eduardo Quirino Arguelho de; Almanza, José Carlos Marino; et al. (Anais do Workshop de Visão Computacional (WVC), 2023)
The search for the automation of processes within fish farms has encouraged the research of new methods for counting fingerlings. The purpose of these devices is to reduce manual labor, increase counting precision and reduce fish stress. The automatic counting system consists of software that uses computer vision techniques to process captured images and a mechanical structure to manipulate fingerlings. A difficulty encountered in image processing is the influence of lighting, which may vary according to the environment, position, and time of day that the device is used. In this paper, we vary the illumination intensity, measured by luxmeter, to identify if this variation interferes in the counting precision. We analyzed five video blocks recorded in the Pacu Project environment in Terenos-MS. A MSE of 9.85 was achieved. The conclusion was that the illumination interferes in the recognition of fingerlings in the video and, consequently, in the counting.